Diffusion driven nanostructuring of metal-organic frameworks (MOFs) for graphene hydrogel based tunable heterostructures: highly active electrocatalysts for efficient water oxidation - Sikdar, Anirban; Majumdar, Abhisek; Gogoi, Abhijit; Dutta, Pronoy; Borah, Munu; Maiti, Soumen; Gogoi, Chiranjib; Reddy, K. Anki; Oh, Youngtak; Maiti, Uday Narayan (ROYAL SOC CHEMISTRY, 2021)
Exposing the surface states of metal-organic frameworks (MOFs) by tuning the shape and size of their nanostructures is expected to enhance their functionalities in practical applications. Herein, a highly scalable 'hydrogel-organic interfacial diffusion' driven approach is utilized for direct growth of metal-organic framework (MOF) nanocrystals over a porous graphene hydrogel framework with fine structural control. Molecular dynamics (MD) simulation of this heterostructure reveals that, two-stage diffusion (hydrogel-organic interfacial and intra-hydrogel) control of organic ligand molecules and their interaction with the graphene surface play key roles in tunable MOF-hydrogel formation. The resulting tri-metallic MOF-hydrogel-hybrid derived porous aerogel exhibits state-of-the-art oxygen evolution reaction (OER) performance metrics with excellent operational stability in alkaline medium. The overpotential required to achieve a current density of 10 mA cm(-2) is as low as 255 mV and a small Tafel slope of 44.3 mV dec(-1) signifies a very high rate of oxygen evolution reaction. The hydrogel-organic interfacial principle of this material could be applied to produce versatile graphene-MOF heterostructures as well as other diverse functional graphene-gel-nanohybrids (e.g. metal nanoparticles, conducting polymers) with intriguing application prospects.